Technological Sustainability of Introduction of Solar Panel Lights in Parks - Karimov Ulugbek Nurmamatovich; Sadinova Yulduz Abdurahmonovna (International Journal on Integrated Education, 2022)
The article scientifically and theoretically studies the advantages and technological advantages of the introduction of solar panels in parks.